Efektivitas Tindakan Primary Percutaneous Coronary Intervention Pada Pasien Stemi Onset Kurang Dari 6 Jam - Heny Widianingsih; Sahrudi Sahrudi (Universitas Malahayati Lampung, 2022)
ABSTRACT In ST-elevation myocardial infarction patients, there is a sudden decrease in coronary blood flow due to thrombus occlusion in a preexisting atherosclerotic plaque. Efforts to reduce the death rate from coronary heart disease continue to be developed, starting from reducing risk factors, medical therapy to heart surgery. One of the most commonly used methods is cardiac catheterization, including Percutaneous Coronary Intervention (PCI). Purpose To determine the effectiveness of primary PCI in STEMI patients with onset less than 6 hours at Primaya Hospital, West Bekasi in 2021. The design used is a retrospective cohort study. This research was conducted at Primaya Hospital, Bekasi Barat in December 2021. The population is all patients who experienced STEMI at Primaya Hospital Bekasi Barat for the period January-December 2021, were 116 respondents. The sampling technique used a total sampling model. The tool used is by looking at the results of the ECG after and before the primary PCI action in the patient's medical record. The analysis used univariate and bivariate analysis. Research. The results showed that the results of the ECG before the primary PCI was performed showed that all respondents had impaired heart function as many as 116 (100%). The results of the ECG after the primary PCI was performed, some of the respondents did not experience heart function disorders as many as 111 (95.7%) respondents. There is an effect of primary PCI action on STEMI patients with onset less than 6 hours at Primaya Hospital, West Bekasi in 2021 with a p-value of 0.000. The results of this study are expected to serve as objective information regarding the effectiveness of primary PCI in STEMI patients with onset less than 6 hours. Keywords: Primary, Percutaneous Coronary Intervention, Elektrokardiograf ABSTRAK Pada pasien ST elevation myocardial infarction, terjadi penurunan aliran darah koroner secara mendadak akibat oklusi trombus pada plak aterosklerotik yang sudah ada sebelumnya. Upaya dalam penurunan tingkat kematian akibat penyakit jantung koroner terus dikembangkan mulai dari penurunan faktor risiko, terapi medis sampai operasi jantung. Salah satu metode yang paling umum digunakan adalah kateterisasi jantung antara lain Percutaneous Coronary Intervention (PCI). Tujuan Untuk mengetahui efektivitas tindakan primary PCI pada pasien ST elevation myocardial infarction onset kurang dari 6 jam di RS Primaya Bekasi Barat tahun 2021. Desain yang digunakan adalah retrospektif kohort study. Penelitian ini dilakukan di RS Primaya Bekasi Barat pada Desember 2021. Populasi yaitu seluruh pasien yang mengalami ST elevation myocardial infarction di RS Primaya Bekasi Barat periode Januari-Desember 2021 sebanyak 116 responden dengan tekhnik sampling yaitu Total Sampling. Data dikumpulkan dengan menganalisis hasil EKG setelah dan sebelum dilakukan tindakan primary PCI pada rekam medis pasien. Analisis yang digunakan analisis univariat dan bivariat. Hasil penelitian menunjukan bahwa hasil EKG sebelum dilakukan primary PCI menunjukan semua responden mengalami gangguan fungsi jantung sebanyak 116 (100%). Hasil EKG setelah dilakukan tindakan primary PCI sebagian responden tidak terjadi gangguan fungsi jantung sebanyak 111 (95,7%) responden. Ada pengaruh tindakan tindakan primary PCI pada pasien ST elevation myocardial infarction onset kurang dari 6 jam di RS Primaya Bekasi Barat tahun 2021 dengan nilai p value 0,000. Hasil penelitian ini diharapkan dapat dijadikan sebagai informasi yang objektif mengenai efektifitas tindakan primary PCI pada pasien Percutaneous Coronary Intervention, Elektrokardiograf, ST elevation myocardial infarction onset kurang dari 6 jam Kata kunci: Primary, Percutaneous Coronary Intervention, Elektrokardiograf